2007
DOI: 10.1111/j.1365-2400.2007.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

How do fish exploit temporary waters throughout a flooding episode?

Abstract: Temporary waters are important habitats for many fish species. Nevertheless, determination of which species colonise these habitats, when this occurs and where fish distribute themselves within the temporary waters are rare. The fish assemblage on a temporarily flooded grassland and its adjacent permanent canal, together with environmental variables, were monitored throughout an entire flooding event from February to May 2006 in the Brie`re marsh (Northwest France). In total, 589 fish belonging to 12 species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…For example, consistent low flows may give an impression of ecological health, but in fact dampen biotic responses to larger events . Similarly, small flow events may disproportionately benefit alien fish species, if native species do not utilize floodplain habitats until water quality conditions have stabilized ( Figure 9; Gehrke, 1991;Jenkins and Wolfenden, 2006) and water depths are suitable (Cucherousset et al, 2007a). Given these constraints, the wisest use of small environmental flows for native fish outcomes in aridzone rivers might be to target specific refuge habitats which sustain fish through droughts, rather than inundating shallow floodplain areas for shorter time periods.…”
Section: Discussionmentioning
confidence: 95%
“…For example, consistent low flows may give an impression of ecological health, but in fact dampen biotic responses to larger events . Similarly, small flow events may disproportionately benefit alien fish species, if native species do not utilize floodplain habitats until water quality conditions have stabilized ( Figure 9; Gehrke, 1991;Jenkins and Wolfenden, 2006) and water depths are suitable (Cucherousset et al, 2007a). Given these constraints, the wisest use of small environmental flows for native fish outcomes in aridzone rivers might be to target specific refuge habitats which sustain fish through droughts, rather than inundating shallow floodplain areas for shorter time periods.…”
Section: Discussionmentioning
confidence: 95%
“…The important role played by periodically inundated or temporary habitats as fish nursery and feeding areas has been demonstrated (Cucherousset et al 2007), as has the role of isolated waterbodies as refugia from disturbance associated with drying (Magoulick & Kobza 2003;Dekar & Magoulick 2007). However, despite the recognized ecological value of temporary habitats, prior studies have not considered entirely ephemeral catchments, nor the behaviour of their resident biota through time.…”
Section: Discussionmentioning
confidence: 96%
“…Fish communities in wetland habitats are known to change throughout the flooding period (Baber et al, 2002). Several studies have already shown that highest abundances and dispersions of fish on wetland habitats occur in the middle of the flooding period (Crain et al, 2004;Cucherousset et al, 2007a). Consequently and despite some differences in flooding patterns between the two years, fish sampling operations were carried out on wetland habitats (eleven grasslands and seven reed beds) from early to mid-April in 2004 and 2005 (mean water depth of 46.6 (AE 13.7 SD) and 26.9 (AE 8.4 SD) cm, respectively).…”
Section: Fish Samplingmentioning
confidence: 98%
“…PAS aims to provide semi-quantitative samples, and hence permits the comparison of sampling points, within and between sites as long as sufficient samples are taken from a range of habitats (Copp, 1989;Perrow et al, 1996;Garner, 1997). Consequently, a total of 665 PAS were performed in canals (25.6 AE 3.8 SD per site) and 1156 PAS in wetland habitats (32.1 AE 6.0 SD per site) to standardize the sampling effort between sites (%0.4 PAS.100 m À2 , Cucherousset et al, 2007a). Fish were collected with a net, identified for species, measured to the nearest mm and always released back into the water immediately and behind the operators.…”
Section: Fish Samplingmentioning
confidence: 99%